Long cycle aqueous zinc-ion battery cathode material and preparation method thereof
Patent Information
- Application Number
- CN202610929813.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
[0002]当前在直接转变化学能为电能的方法与装置中,水系锌离子电池正极材料的制备通常采用常规共沉淀反应合成多晶前驱体,常规工艺以搅拌方式维持反应体系内部的空间热力学平衡,使离子沿表面最低能量晶面方向有序排列,以获得组分均匀且晶格结构完整的晶态活性储能颗粒,在恒定工况下,此均一结构提供稳定的锌离子传质通道,保障储能装置具备常规指标,实现基础容量与能量转换效率,然而,在频繁大容量充放电交替的宽温变储能工况下,活性颗粒固液界面承受强库仑力引起的连续不对称晶格应力,在此工况中,由于传统工艺产出的正极材料内部晶格位向高度一致,系统内部天然缺乏对应变畸变的柔性消纳与多维缓冲机制,各向异性应变沿特定晶轴较易发生非对称性空间积聚,从而在缺陷边界区域产生较大的局部集中应力,引发多晶颗粒内部产生剥离裂纹,导致材料结构粉化崩塌,缩短储能装置循环寿命,更会加剧过渡金属元素在电解液中的溶解,伴生副反应沉淀物阻塞传质孔道
[0019]1、在长循环水系锌离子电池正极材料的制备中,控制金属盐前驱体水溶液以恒定流量持续注入,调配沉淀剂水溶液以脉冲流量周期性交替引入高剪切错流分散流道,配合设定剪切速率使流体发生非均相局部快速成核,高流量阶段的局域过饱和度越过非晶化势垒以产生富含缺陷的柔性无定形相,零流量静息阶段伴随化学势弛豫使游离金属离子依附既有核表面长程有序排列成刚性晶态骨架,由此形成外部非晶态网络减震层与内部晶态承重骨架原位键合的复合形态,用以分摊强库仑力引起的局部集聚应力,免除正极材料粉化开裂缺陷。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention relates to a positive electrode material for a long-cycle aqueous zinc-ion battery and its preparation method, belonging to the technical field of energy storage devices that directly convert chemical energy into electrical energy. Background Technology
[0002] Currently, in methods and devices for directly converting chemical energy into electrical energy, the preparation of aqueous zinc-ion battery cathode materials typically employs conventional co-precipitation reactions to synthesize polycrystalline precursors. Conventional processes maintain the spatial thermodynamic equilibrium within the reaction system through stirring, ensuring that ions are orderly arranged along the lowest energy crystal plane to obtain crystalline active energy storage particles with uniform composition and a complete crystal lattice structure. Under constant operating conditions, this uniform structure provides stable zinc-ion mass transfer channels, guaranteeing that the energy storage device meets conventional specifications and achieves basic capacity and energy conversion efficiency. However, under wide-temperature-varying energy storage conditions with frequent high-capacity charge-discharge cycles… The solid-liquid interface of active particles is subjected to continuous asymmetric lattice stress caused by strong Coulomb forces. Under this condition, due to the highly uniform lattice orientation of the cathode material produced by traditional processes, the system naturally lacks a flexible absorption and multidimensional buffering mechanism for strain distortion. Anisotropic strain is more likely to accumulate asymmetrically along a specific crystal axis, resulting in large localized stress concentration in the defect boundary region. This causes peeling cracks to form inside the polycrystalline particles, leading to the pulverization and collapse of the material structure, shortening the cycle life of the energy storage device, and further exacerbating the dissolution of transition metal elements in the electrolyte. Accompanying side reaction precipitates block the mass transfer channels.
[0003] To overcome the problem of lattice pulverization and cracking, the industry often attempts to physically coat the surface of active particles with a metal oxide protective layer or introduce exogenous heteroatoms. However, the physical adhesion layer and the active center have obvious lattice mismatches, which can easily cause interfacial delamination failure and lead to an increase in mass transfer impedance during thermal cycling. Although overall uniform doping can change the local chemical bond length to suppress the initial lattice distortion, it is more likely to trigger harmful phase segregation. This creates an exclusive physical constraint that makes it impossible to reconcile the long-range rigid support capacity of the active material's lattice with the flexible absorption and buffering performance of the solid-liquid interface. Although hardware improvements to the shear components inside the reaction equipment can optimize the overall flow field, there are still shortcomings in the flow timing control method. For example, Chinese invention patent application with publication number CN117878237A Please disclose a novel vanadium-based aqueous zinc-ion battery cathode and its preparation method. The amorphous cathode material is prepared by conventional constant-rate dropping and overall magnetic stirring process. This process relies on a uniform mass transfer environment. Under the dynamic evolution scenario of scale-up production, the overall disordered mixing leads to local supersaturation aggregation and concentration gradient at the feeding port. Due to the lack of transient regulation of the local nucleation rate by surface shear dynamics and the lack of time-series fluctuation control to introduce chemical potential relaxation period, the resulting phase exhibits a single homogeneous and completely amorphous structure. Under the strong Coulomb force impact of frequent high-capacity charge and discharge, the pure amorphous phase structure lacks an ordered rigid crystalline framework as a load-bearing support, which triggers irreversible phase transformation and structural collapse. This exacerbates the liquid phase dissolution of active elements under wide temperature variation conditions and cannot simultaneously take into account the flexible strain absorption of the solid-liquid interface and the rigidity of the framework.
[0004] Therefore, controlling the coprecipitation crystallization kinetics process to construct a composite heterogeneous phase structure that combines a crystalline support framework and an amorphous buffer shell in situ is the technical problem to be solved by this invention. Summary of the Invention
[0005] To address the problems in the background art, the technical solution of the present invention is as follows: A method for preparing a positive electrode material for a long-cycle aqueous zinc-ion battery, comprising the following steps:
[0006] Step S1: A vanadium sulfate aqueous solution with deionized water as solvent and a total molar concentration of metal ions of 1.5 mol / L to 2.5 mol / L is continuously pumped into a high-shear cross-flow dispersion channel at a constant flow rate.
[0007] Step S2: A sodium hydroxide precipitant aqueous solution with a molar concentration of 1.0 mol / L to 3.0 mol / L, using deionized water as the solvent, is periodically and alternately pumped into a high-shear cross-flow dispersion channel at a pulsed flow rate. The sodium hydroxide precipitant aqueous solution is dispersed within 10 ms and mixed with a vanadium sulfate aqueous solution to carry out a liquid-phase co-precipitation reaction, generating a solid-liquid mixed suspension. The pulsed flow rate follows a stepped square wave distribution on the time axis, and the timing unit of the pulsed flow rate dripping cycle includes a high flow rate dripping stage lasting 15 s to 30 s and a zero flow rate resting stage lasting 45 s to 90 s.
[0008] Step S3: The solid-liquid mixed suspension is continuously guided into a closed reaction vessel and subjected to cross-flow stirring reaction at a temperature of 50°C to 75°C for 4 to 8 hours. After washing and drying, the long-cycle aqueous zinc-ion battery cathode material is obtained.
[0009] Preferably, in step S2, during the high-flow-rate dripping stage, the transient feed flow rate of the sodium hydroxide precipitant aqueous solution is dynamically adjusted according to the monitored hydrogen ion concentration index of the solid-liquid mixed suspension, so that the hydrogen ion concentration index of the solid-liquid mixed suspension is maintained in the range of 7.5 to 8.5.
[0010] Preferably, during the zero-flow resting phase in step S2, a multi-stage doped modifier aqueous solution is pumped into the high-shear cross-flow dispersion channel; the modified metal ions in the multi-stage doped modifier aqueous solution include aluminum ions and lanthanum ions, and the total molar concentration of the modified metal ions in the multi-stage doped modifier aqueous solution is 0.01 mol / L to 0.10 mol / L.
[0011] Preferably, step S3 includes the following sub-steps: Step S31, the solid-liquid mixed suspension is continuously guided into the sealed reactor and heated by the circulating fluid in the high-pressure jacket outside the sealed reactor, so that the temperature of the reaction material inside the sealed reactor rises to 50°C to 75°C; Step S32, the propeller blades inside the sealed reactor are started to perform counter-current cross-flow stirring, and the rotation speed of the propeller blades is controlled to be 150 rpm to 300 rpm, the temperature is maintained and the material co-precipitation and solidification reaction is continued for 4 h to 8 h; Step S33, the pneumatic discharge valve at the bottom of the sealed reactor is opened in conjunction to discharge the solidified reaction product and obtain the cathode material precursor slurry.
[0012] Preferably, step S3 further includes the following sub-steps: Step S34, the cathode material precursor slurry is fed into a vacuum filter for solid-liquid separation, and the separated filter cake is washed alternately with deionized water and anhydrous ethanol as detergents 3 to 5 times, and the washed precursor solid is collected; Step S35, the washed precursor solid is placed in a double-layer multi-temperature controlled vacuum drying oven, and is dried at a constant temperature of 60°C to 80°C and a vacuum degree of not less than 0.09MPa for 12 to 24 hours to obtain a long-cycle aqueous zinc-ion battery cathode material.
[0013] Preferably, the molar ratio of zinc to manganese in the vanadium sulfate aqueous solution is 1:2 to 1:4; and the vanadium sulfate aqueous solution also contains sodium sulfate with a molar concentration of 0.1 mol / L to 0.5 mol / L, which is used as a crystal anisotropic growth guiding agent.
[0014] Preferably, in step S1, the high-shear cross-flow dispersion channel is achieved by using a twin-screw grinding cross-flow pump connected in the same direction or a high-shear inline emulsifier, and the electromagnetic pulse feed valve port for injecting the sodium hydroxide precipitant aqueous solution is directly aligned with the fluid shear zone with the greatest shear force inside the high-shear cross-flow dispersion channel.
[0015] Preferably, in step S1, the ambient fluid temperature is maintained between 25°C and 40°C when the vanadium sulfate aqueous solution is pumped into the high-shear cross-flow dispersion channel, and the pumping flow rate of the sodium hydroxide precipitant aqueous solution is controlled to be between 10 mL / min and 30 mL / min during the high-flow-rate dripping stage.
[0016] Preferably, in step S2, during the injection of a multi-stage doped modifier aqueous solution into the high-shear cross-flow dispersion channel, an external jacketed ultrasonic transducer is activated to emit ultrasonic waves with a pulse power of 100W to 200W into the reactive fluid inside the high-shear cross-flow dispersion channel, and the activation sequence of the ultrasonic waves is controlled to be synchronized with the duration of the zero-flow resting phase.
[0017] A long-cycle aqueous zinc-ion battery cathode material is prepared by a method for preparing a long-cycle aqueous zinc-ion battery cathode material.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. In the preparation of positive electrode materials for long-cycle aqueous zinc-ion batteries, the aqueous solution of metal salt precursor is continuously injected at a constant flow rate, and the aqueous solution of precipitant is periodically and alternately introduced into a high-shear cross-flow dispersion channel at a pulsed flow rate. With the set shear rate, the fluid undergoes heterogeneous local rapid nucleation. During the high flow rate stage, the local supersaturation exceeds the amorphization barrier to produce a flexible amorphous phase rich in defects. During the zero flow rate resting stage, the chemical potential relaxation causes free metal ions to adhere to the existing nucleus surface and arrange themselves in a long-range ordered manner to form a rigid crystalline framework. This forms a composite morphology in which the external amorphous network damping layer and the internal crystalline load-bearing framework are bonded in situ. This is used to distribute the localized stress caused by strong Coulomb forces and avoid the pulverization and cracking defects of the positive electrode material.
[0020] 2. By using the strong shear flow field provided by the high-shear cross-flow dispersion channel, the shear rate inside the channel is set, allowing the precipitant to be dispersed into the precursor solution. The strong shear action eliminates the inhomogeneity caused by the overall mass transfer resistance, avoiding local oversaturation aggregation at the feed port. This allows the flexible amorphous phase shell produced by the solidification reaction to continuously wrap around the surface of the crystalline framework. This interface does not undergo interlayer delamination due to long-term charge-discharge fatigue. Under wide temperature variation conditions, the charge distribution at the solid-liquid interface is regulated by saturated coordination, blocking the attack of water molecules on transition metal elements and inhibiting the phenomenon of hydrogen evolution side reaction precipitation aggregation blocking ion transport channels.
[0021] 3. During the zero-flow resting phase, the auxiliary injection valve is opened to introduce a multi-stage doped modifier aqueous solution. The injection volume is controlled to meet a specific linear mapping ratio with the cumulative mass of precipitant injected in the preceding high-flow droplet stage. Specific modified ions are pinned in situ in the amorphous network by utilizing the unsaturated coordination state of the amorphous phase layer. This widens the pore size of the amorphous network and reduces the low-temperature mass transfer resistance during the reaction. By interlocking and adjusting the ion implantation amount with the thickness of the amorphous layer generated by the preceding pulse, the modified cathode material electrostatically repels the outer water molecules of hydrated zinc ions when in contact with the aqueous electrolyte, eliminating the potential fault of side reactants accumulating and blocking the mass transfer channels under high-frequency temperature variation conditions. Attached Figure Description
[0022] Figure 1 This is a flowchart of the cathode material preparation method of the present invention;
[0023] Figure 2 This is a graph showing the change in charge transfer resistance of the control group and the experimental group of this invention with the number of cycles.
[0024] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0025] The technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application are within the scope of protection of this application.
[0026] A method for preparing a cathode material for a long-cycle aqueous zinc-ion battery includes the following steps:
[0027] Step S1: A vanadium sulfate aqueous solution with deionized water as solvent and a total molar concentration of metal ions of 1.5 mol / L to 2.5 mol / L is continuously pumped into a high-shear cross-flow dispersion channel at a constant flow rate.
[0028] Step S2: A sodium hydroxide precipitant aqueous solution with a molar concentration of 1.0 mol / L to 3.0 mol / L, using deionized water as the solvent, is periodically and alternately pumped into a high-shear cross-flow dispersion channel at a pulsed flow rate. The sodium hydroxide precipitant aqueous solution is dispersed within 10 ms and mixed with a vanadium sulfate aqueous solution to carry out a liquid-phase co-precipitation reaction, generating a solid-liquid mixed suspension. The pulsed flow rate follows a stepped square wave distribution on the time axis, and the timing unit of the pulsed flow rate dripping cycle includes a high flow rate dripping stage lasting 15 s to 30 s and a zero flow rate resting stage lasting 45 s to 90 s.
[0029] Step S3: The solid-liquid mixed suspension is continuously guided into a closed reaction vessel and subjected to cross-flow stirring reaction at a temperature of 50°C to 75°C for 4 to 8 hours. After washing and drying, the long-cycle aqueous zinc-ion battery cathode material is obtained.
[0030] Preferably, in step S2, during the high-flow-rate dripping stage, the transient feed flow rate of the sodium hydroxide precipitant aqueous solution is dynamically adjusted according to the monitored hydrogen ion concentration index of the solid-liquid mixed suspension, so that the hydrogen ion concentration index of the solid-liquid mixed suspension is maintained in the range of 7.5 to 8.5.
[0031] Preferably, during the zero-flow resting phase in step S2, a multi-stage doped modifier aqueous solution is pumped into the high-shear cross-flow dispersion channel; the modified metal ions in the multi-stage doped modifier aqueous solution include aluminum ions and lanthanum ions, and the total molar concentration of the modified metal ions in the multi-stage doped modifier aqueous solution is 0.01 mol / L to 0.10 mol / L.
[0032] Preferably, step S3 includes the following sub-steps: Step S31, the solid-liquid mixed suspension is continuously guided into the sealed reactor and heated by the circulating fluid in the high-pressure jacket outside the sealed reactor, so that the temperature of the reaction material inside the sealed reactor rises to 50°C to 75°C; Step S32, the propeller blades inside the sealed reactor are started to perform counter-current cross-flow stirring, and the rotation speed of the propeller blades is controlled to be 150 rpm to 300 rpm, the temperature is maintained and the material co-precipitation and solidification reaction is continued for 4 h to 8 h; Step S33, the pneumatic discharge valve at the bottom of the sealed reactor is opened in conjunction to discharge the solidified reaction product and obtain the cathode material precursor slurry.
[0033] Preferably, step S3 further includes the following sub-steps: Step S34, the cathode material precursor slurry is fed into a vacuum filter for solid-liquid separation, and the separated filter cake is washed alternately with deionized water and anhydrous ethanol as detergents 3 to 5 times, and the washed precursor solid is collected; Step S35, the washed precursor solid is placed in a double-layer multi-temperature controlled vacuum drying oven, and is dried at a constant temperature of 60°C to 80°C and a vacuum degree of not less than 0.09MPa for 12 to 24 hours to obtain a long-cycle aqueous zinc-ion battery cathode material.
[0034] Preferably, the molar ratio of zinc to manganese in the vanadium sulfate aqueous solution is 1:2 to 1:4; and the vanadium sulfate aqueous solution also contains sodium sulfate with a molar concentration of 0.1 mol / L to 0.5 mol / L, which is used as a crystal anisotropic growth guiding agent.
[0035] Preferably, in step S1, the high-shear cross-flow dispersion channel is achieved by using a twin-screw grinding cross-flow pump connected in the same direction or a high-shear inline emulsifier, and the electromagnetic pulse feed valve port for injecting the sodium hydroxide precipitant aqueous solution is directly aligned with the fluid shear zone with the greatest shear force inside the high-shear cross-flow dispersion channel.
[0036] Preferably, in step S1, the ambient fluid temperature is maintained between 25°C and 40°C when the vanadium sulfate aqueous solution is pumped into the high-shear cross-flow dispersion channel, and the pumping flow rate of the sodium hydroxide precipitant aqueous solution is controlled to be between 10 mL / min and 30 mL / min during the high-flow-rate dripping stage.
[0037] Preferably, in step S2, during the injection of a multi-stage doped modifier aqueous solution into the high-shear cross-flow dispersion channel, an external jacketed ultrasonic transducer is activated to emit ultrasonic waves with a pulse power of 100W to 200W into the reactive fluid inside the high-shear cross-flow dispersion channel, and the activation sequence of the ultrasonic waves is controlled to be synchronized with the duration of the zero-flow resting phase.
[0038] A long-cycle aqueous zinc-ion battery cathode material is prepared by a method for preparing a long-cycle aqueous zinc-ion battery cathode material.
[0039] Example 1: This invention provides a method for preparing a long-cycle aqueous zinc-ion battery cathode material, applicable to electrochemical energy storage scenarios. In the specific preparation process, a 2.0 mol / L vanadium sulfate aqueous solution and a 1.5 mol / L sodium hydroxide aqueous solution are prepared using deionized water as the solvent. Specifically, when preparing the 2.0 mol / L vanadium sulfate aqueous solution using deionized water, a specific mass of manganese sulfate monohydrate and zinc sulfate heptahydrate solids are added and completely dissolved to obtain the final mixed aqueous solution. In this solution, the molar ratio of zinc (in the form of soluble divalent zinc ions) to manganese (in the form of soluble divalent manganese ions) is precisely 1:2. Meanwhile, the concentration of vanadium in the mixed solution remains at the nominal molar concentration, primarily composed of vanadium sulfate. To ensure the absolute mass ratio of each component in the mixed aqueous solution and to control the total molar concentration of metal ions within a specified range, in this specific embodiment, 1 L of deionized water is selected as the solvent to dissolve 1.5 mol of vanadium sulfate solid. Then, 67.61 g of manganese sulfate monohydrate solid and 57.51 g of zinc sulfate heptahydrate solid are added and dissolved. The molar concentrations of vanadium, manganese, and zinc in the mixed aqueous solution were 1.5 mol / L, 0.4 mol / L, and 0.2 mol / L, respectively. The total molar concentration of metal ions in the mixed aqueous solution reached 2.1 mol / L, with the molar ratio of zinc to manganese maintained at 1:2. Under these conditions, the matrix elements and the multi-level doped modifying elements formed a dynamic equilibrium of co-precipitation concentrations. The vanadium sulfate aqueous solution was continuously pumped into the high-shear cross-flow dispersion channel at a constant flow rate of 40 mL / min. Simultaneously, an electromagnetic pulse feeding valve was activated to control the periodic alternating pumping of sodium hydroxide aqueous solution at a pulsed flow rate. The flow rate includes a high-flow-rate dripping phase of 80 mL / min for 20 seconds, followed by a resting phase with a flow rate of 0 for 60 seconds. In actual operation, the 80 mL / min flow rate set during the high-flow-rate dripping phase serves as the nominal upper limit of the square wave for that phase. During this 20-second duration, the control system does not consistently execute constant flow delivery but instead performs micro-adjustments based on the hydrogen ion concentration index monitored in real time by online sensors. When the detected value approaches 7.5, the current transient feed rate is automatically reduced to 75 mL / min, and when the detected value approaches 8...At 5 o'clock, the flow rate was increased to 85 mL / min, resulting in a sawtooth-shaped, continuously adjustable characteristic at the top of the square wave flow rate, fluctuating closely around the reference value. This ensured a constant reaction environment while maintaining the square wave timing architecture. The shear rate in the high-shear cross-flow dispersion channel was set to 3500 rpm. This shearing action uniformly dispersed the sodium hydroxide solution within 10 ms, allowing the local supersaturation to overcome the amorphization barrier and generate a vacancy-rich amorphous network phase. Although the vanadium sulfate aqueous solution was continuously input at a constant flow rate, Because the output pipe at the rear end of the high-shear cross-flow dispersion channel has a specific flow extension volume, the locally reacted material, which is instantaneously sheared, dispersed, and nucleated during the high-flow-rate dripping stage, encounters a resting phase with zero precipitant flow rate on the spatiotemporal propulsion axis of the pipe flow as it moves forward with the fluid out of the high-shear core region. At this point, due to the lack of transient replenishment of high-intensity, high-concentration precipitant, the supersaturation in the local micro-region drops sharply, triggering chemical potential relaxation. This allows the material in this flow section sufficient time to settle and recover during the 60-second flow process.
[0040] The reaction system is in a static relaxation state, where free metal ions adhere to the existing nuclei and arrange themselves in a long-range ordered manner, generating a rigid crystalline framework. This forms a composite structure where an amorphous network damping layer and a crystalline load-bearing framework are bonded in situ. During this resting phase, the auxiliary injection valve is simultaneously opened, introducing a 0.05 mol / L mixture of aluminum and lanthanum ions into the flow channel. The introduced volume satisfies a linear mapping relationship between the proportionality constant 0.08 mL / g and the mass of the precipitant injected in the previous dropwise stage. Specifically, the aforementioned proportionality constant 0.08 mL / g is an engineering boundary value calculated by measuring the theoretical adsorption capacity of the unsaturated coordinate bonds on the surface of the amorphous phase. This linear mapping relationship is specifically controlled by the control system. The software algorithm executes logic by continuously accumulating the total mass of sodium hydroxide precipitant pumped in during the preceding 20-second high-flow-rate dripping phase and multiplying it by 0.08 to directly calculate the nominal volume (in milliliters) of the mixed modified solution required for the current resting phase. If the resting time is shortened or the precipitant mass is reduced, the injection volume of the modified solution is proportionally reduced. This ensures that the introduced modified metal ions are precisely pinned in situ within the amorphous network defects without causing excessive phase segregation. To verify the aforementioned optimal range of total metal ion molar concentration and the distribution ratios of each group, a control experiment is conducted to verify the performance. When the total molar concentration of metal ions in the mixed aqueous solution drops below 1.5 mol / L, due to the nucleation of the reactants... Insufficient driving force and a thickness of less than 2 nm for the amorphous network damping layer prevent the distribution of lattice volume stress generated during repeated zinc ion insertion / extraction, leading to through-cracks in the material after 500 cycles. When the total molar concentration of metal ions in the mixed aqueous solution rises above 2.5 mol / L, high-concentration local supersaturation causes co-precipitated reactants to aggregate within 10 ms, with the amorphous phase volume fraction exceeding 60% in the product. Due to the lack of long-range support from a rigid crystalline framework, the cathode material experiences surface structure collapse during long-term charge-discharge cycles, causing the charge transfer resistance to rise from the initial 42.8 ohms to over 180 ohms. Data indicates that controlling the total molar concentration of metal ions between 1.5 mol / L and 2.5 mol / L is crucial. Within the range of / L, the formulation and process work in synergy to enable the cathode material to form a gradient topological heterostructure in situ bonding between the crystalline phase framework and the amorphous phase shell. This creates a working window that balances flexible strain absorption and rigid framework support. The suspension output from the flow channel is continuously guided into a closed reactor. The material temperature is maintained at 65℃ by jacket heating. The propeller blades are started to stir in a counter-current flow at a speed of 250 rpm for 6 hours. The pneumatic discharge valve is then opened to discharge the solidified product. The resulting precursor slurry is sent to a vacuum filter for solid-liquid separation. The filter cake is washed four times alternately with deionized water and anhydrous ethanol. The filter cake is collected, and the precursor solid is placed in a double-layer multi-temperature controlled vacuum drying oven at a drying temperature of 70℃ and a vacuum degree of 0.The cathode material was dried at 0.95 MPa for 18 hours to obtain the finished product. Under a test condition of 10 A / g, the material retained 90.1% of its capacity and had a coulombic efficiency of 99.9% after 2000 cycles. To confirm the in-situ bonding state between the amorphous phase shell and the crystalline phase framework, a purely digital stepwise fitting procedure based on standard electrochemical impedance spectroscopy was used for objective quantitative characterization. In a static state without fluid interference, a digital verification matrix was established based on the evolution of charge transfer impedance in the high-frequency region. Experiments showed that the initial charge transfer impedance of the finished cathode material was stable at 42.8 ohms. Furthermore, after 100, 500, and 2000 high-current charge-discharge cycles, the absolute difference in the fluctuation of the fitted heterogeneous phase interface impedance was consistently less than 5.5 ohms. This constant numerical difference directly proves, in physical terms, the existence of a high-strength atomic-level chemically bonded transition layer at the two-phase interface, rather than a fragile physical stacking coating structure.
[0041] Example 2: This invention provides a comparative experiment to verify the structural stability of the cathode material in a long-cycle aqueous zinc-ion battery. The experiment is conducted in an electrochemical energy storage environment simulating actual energy storage conditions. By observing the physical evolution of the control and experimental groups during cycling, the performance gain mechanism of the in-situ bonding between the amorphous network damping layer and the crystalline load-bearing framework is revealed. The experimental platform consists of an electrochemical workstation, a high-precision cycling tester, and a scanning electron microscope. The test environment temperature is controlled at 45.0℃. In the parameter setting stage, both the experimental and control groups use vanadium sulfate aqueous solution and hydroxide... Sodium was used as both a precursor and a precipitant. In the control group, a continuous dripping process was used, with the sodium hydroxide solution as the precipitant continuously pumped into the high-shear cross-flow dispersion channel at a constant flow rate of 100.0 mL / min. In the experimental group, the aforementioned pulsed flow process was followed, with a high flow rate of 80.0 mL / min for 20.0 s and a resting phase of 0 flow rate for 60.0 s. By controlling the chemical potential through this nonlinear time sequence, the shear rate of the channel was set to 3500 rpm. This shearing action caused the sodium hydroxide solution to be uniformly dispersed within 10.0 ms, inducing local supersaturation.
[0042] Experimental data showed that in the control group, through-cracks appeared on the surface of the cathode material particles after 500 cycles, and scanning electron microscopy of the electrode cross-section showed obvious phase delamination. The corresponding charge transfer resistance increased from the initial 45.2Ω to 215.6Ω. In contrast, under the same test conditions, the experimental group maintained the integrity of the material particle morphology, and the charge transfer resistance increased from the initial 42.8Ω to 58.3Ω. Regarding the numerical range boundary, when the precipitant pulse rest time was shortened to below 10.0s, the coverage thickness of the amorphous network damping layer was insufficient, and the capacity retention rate of the material dropped to 82.5% after 200 cycles, with obvious polarization intensification. When the pulse rest time was extended to above 120.0s, the crystalline load-bearing skeleton grew too large, resulting in a decrease in the specific surface area of the material, and the initial discharge capacity at a current density of 10.0A / g decreased by about 15.4%.
[0043] Test results show that when the ratio of the precipitant pulse flow rate to the resting phase time is in the range of 0.25 to 0.35, the amorphous network damping layer can form a uniform coating structure. The coulombic efficiency of the material at a current density of 10.0 A / g remains above 99.5%. This confirms that the amorphous shell has isotropic volume capacity, which can absorb the lattice stress during zinc ion insertion. Moreover, the chemical bond structure with the crystalline core does not undergo interface debonding during cycling, maintaining a stable solid-liquid interface charge distribution and inhibiting the liquid phase dissolution of active metal ions.
[0044] Example 3: This example combines Figures 1 to 2 This paper describes a cathode material for a long-cycle aqueous zinc-ion battery and its preparation method. Figure 1 As shown, a vanadium sulfate aqueous solution, using deionized water as a solvent, is continuously pumped into a high-shear cross-flow dispersion channel at a constant flow rate. Simultaneously, a sodium hydroxide precipitant aqueous solution is periodically and alternately pumped into the same high-shear cross-flow dispersion channel with a stepped square wave pulse flow rate along the time axis. Under internal shear rates of 3000 rpm to 4500 rpm, dispersion and liquid-phase co-precipitation reaction occur within 10 ms. The resulting solid-liquid mixed suspension reaction intermediate is continuously guided to the next processing unit, entering a closed reactor for cross-flow stirring. The reaction is carried out at a temperature of 50°C to 75°C for a duration of 4 to 8 hours. The reacted material is then sent to a washing and drying unit. After washing and drying, the final cathode material is obtained. This long-cycle aqueous zinc-ion battery cathode material is used in energy storage devices that directly convert chemical energy into electrical energy.
[0045] like Figure 2As shown, the graph uses the number of cycles as the horizontal axis with a value range of 0 to 500, and the charge transfer resistance (Ω) as the vertical axis with a value range of 0 to 250. The graph includes two curves: one for the control group and one for the experimental group. The curve for the control group is a solid line, and the curve for the experimental group is a dashed line. This is used to show the changing trend of the charge transfer resistance corresponding to the control group and the experimental group under different numbers of cycles.
[0046] Example 4: In the operating scenario of long-cycle aqueous zinc-ion battery cathode materials, the lattice volume stress generated during the repeated insertion and extraction of zinc ions leads to the accumulation of microcracks inside the particles, which in turn causes the dissolution of active vanadium species. This problem is particularly significant in the high-frequency and wide-temperature-varying operating environment. In order to improve the structural integrity and chemical stability of the material, this invention introduces microfluidic shear and chemical potential energy oscillation during the precipitation reaction to construct a composite heterogeneous phase with a gradient structure in situ.
[0047] A 2.0 mol / L vanadate aqueous solution and a 1.5 mol / L sodium hydroxide precipitant solution were pumped separately into a high-shear cross-flow dispersion channel. The shear rate in the channel was set to 3500 rpm to ensure that the two fluids achieved molecular-level uniform distribution upon contact. To achieve in-situ bonding between the crystalline load-bearing framework and the amorphous network damping layer, a pulsed flow control method was used to regulate the chemical potential. The precipitant flow rate was set to alternate periodically, with a high-flow-rate dropping phase of 80.0 mL / min lasting for 20.0 s and a cut-off flow period of 60 s. During the 0s resting phase, the chemical potential oscillation is controlled by this nonlinear time sequence, allowing the local supersaturation to overcome the amorphization barrier and generate a vacancy-rich amorphous network phase. During the resting phase, the reaction system is in a state of chemical potential relaxation, and free metal ions adhere to the existing nucleus surface for long-range ordered arrangement, generating a rigid crystalline framework. In the middle and late stages of this resting phase, the auxiliary injection valve is opened simultaneously to introduce a mixed modified solution of aluminum and lanthanum ions with a molar concentration of 0.05 mol / L into the flow channel. The injection volume is simultaneously metered based on the proportional constant of 0.08 mL / g per gram of precipitant added.
[0048] The suspension output from the flow channel is continuously guided into a closed reactor. Jacket heating maintains the material temperature at 65.0℃. A propeller-type impeller performs counter-current stirring at 250.0 rpm for 6.0 hours. The solidified product is discharged through a pneumatic discharge valve. The resulting precursor slurry is then subjected to vacuum filtration and alternating washing with deionized water and anhydrous ethanol. The filter cake is collected and placed in a vacuum drying oven at 70.0℃ and 0.095 MPa for 18.0 hours to obtain the finished cathode material. Under a test condition of 10.0 A / g, this… After 2000 cycles, the material retained 90.1% of its capacity and 99.9% of its coulombic efficiency. Scanning electron microscopy revealed no significant delamination at the in-situ bonding interface between the amorphous network damping layer and the crystalline load-bearing skeleton, indicating that the gradient structure effectively absorbed the transient thermal stress caused by zinc ion intercalation / deintercalation. When the shear rate decreased to below 1500 rpm, the thickness of the amorphous network damping layer decreased. After 500 cycles, the charge transfer resistance increased from the initial 42.8 Ω to over 250.0 Ω, confirming the necessity of specific high-shear kinetic conditions for the formation of the gradient phase structure.
[0049] Example 5: In the newly constructed high-frequency wide-temperature variable electrochemical energy storage system, to solve the technical problems of lattice volume stress accumulation and dissolution of active vanadium species generated during the repeated zinc ion insertion / extraction process of the cathode material, this scheme implements a composite heterogeneous phase preparation procedure with an in-situ symbiotic structure. Vanadyl sulfate aqueous solution is selected as the metal salt precursor with a molar concentration of 2.0 mol / L, and sodium hydroxide aqueous solution is selected as the precipitant with a molar concentration of 1.5 mol / L. The vanadium sulfate aqueous solution is pumped into the high-shear cross-flow dispersion channel at a constant flow rate of 40 mL / min. At the same time, the sodium hydroxide aqueous solution is periodically injected into the channel with a square wave pulse flow rate through an electromagnetic pulse feeding valve. The pulse flow rate is set to 80 mL / min during the high-flow-rate dropping stage for 20 s, followed by a zero-flow-rate resting stage for 60 s. The local supersaturation of the reactants is controlled by a shear rate of 3500 rpm in the channel, so that the product generates an amorphous network phase in situ.
[0050] During the aforementioned zero-flow resting phase, the auxiliary injection valve is opened, and a modified liquid mixture of aluminum and lanthanum ions with a molar concentration of 0.05 mol / L is pumped into the flow channel. The injection volume of the modified liquid is calculated based on the proportionality constant of 0.08 mL / g and the cumulative mass of precipitant injected during the previous high-flow-rate dropping phase. The suspension produced in the flow channel is continuously guided into a sealed reactor. At 65°C, it is continuously stirred by a propeller at a speed of 250 rpm for a reaction time of 6 hours. During the reaction, a bonded structure of amorphous shell and crystalline framework is formed. After the reaction, the solidified product is discharged through a pneumatic discharge valve, and solid-liquid separation is performed using a vacuum filter. Deionized water and... The filter cake was alternately rinsed with anhydrous ethanol and placed in a double-layer, multi-temperature-controlled vacuum drying oven. It was dried at 70℃ and 0.095MPa vacuum for 18 hours to obtain the finished cathode material. The cathode material retained a discharge specific capacity of 90.1% and a coulombic efficiency of 99.9% after 2000 cycles at a current density of 10A / g. Scanning electron microscopy showed that the in-situ bonding interface between the amorphous network damping layer and the crystalline load-bearing skeleton was flat. The lattice stress caused by zinc ion insertion was distributed through the isotropic volume containment of the amorphous network layer. The saturated chemical coordination heterostructure of the amorphous shell effectively blocked the dissolution attack path of water molecules on active vanadium species.
[0051] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the present invention.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a positive electrode material for a long-cycle aqueous zinc-ion battery, characterized in that, Includes the following steps: Step S1: A vanadium sulfate aqueous solution with deionized water as solvent and a total molar concentration of metal ions of 1.5 mol / L to 2.5 mol / L is continuously pumped into a high-shear cross-flow dispersion channel at a constant flow rate. Step S2: A sodium hydroxide precipitant aqueous solution with a molar concentration of 1.0 mol / L to 3.0 mol / L, using deionized water as the solvent, is periodically and alternately pumped into a high-shear cross-flow dispersion channel at a pulsed flow rate. The sodium hydroxide precipitant aqueous solution is dispersed within 10 ms and mixed with a vanadium sulfate aqueous solution to carry out a liquid-phase co-precipitation reaction, generating a solid-liquid mixed suspension. The pulsed flow rate follows a stepped square wave distribution on the time axis, and the timing unit of the pulsed flow rate dripping cycle includes a high flow rate dripping stage lasting 15 s to 30 s and a zero flow rate resting stage lasting 45 s to 90 s. Step S3: The solid-liquid mixed suspension is continuously guided into a closed reaction vessel and subjected to cross-flow stirring reaction at a temperature of 50°C to 75°C for 4 to 8 hours. After washing and drying, the long-cycle aqueous zinc-ion battery cathode material is obtained.
2. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, In step S2, during the high-flow-rate dropping stage, the transient feed flow rate of the sodium hydroxide precipitant aqueous solution is dynamically adjusted according to the monitored hydrogen ion concentration index of the solid-liquid mixed suspension, so that the hydrogen ion concentration index of the solid-liquid mixed suspension is maintained in the range of 7.5 to 8.
5.
3. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, During the zero-flow resting phase in step S2, a multi-stage doped modifier aqueous solution is pumped into the high-shear cross-flow dispersion channel; the modified metal ions in the multi-stage doped modifier aqueous solution include aluminum ions and lanthanum ions, and the total molar concentration of the modified metal ions in the multi-stage doped modifier aqueous solution is 0.01 mol / L to 0.10 mol / L.
4. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, Step S3 includes the following sub-steps: Step S31, the solid-liquid mixed suspension is continuously guided into the sealed reactor and heated by the circulating fluid in the high-pressure jacket outside the sealed reactor, so that the temperature of the reaction material inside the sealed reactor rises to 50°C to 75°C; Step S32, the propeller blades inside the sealed reactor are started to stir in a counter-current manner, and the speed of the propeller blades is controlled to be 150 rpm to 300 rpm, maintaining the temperature and continuing the co-precipitation and solidification reaction of the material for 4 to 8 hours; Step S33, the pneumatic discharge valve at the bottom of the sealed reactor is opened in conjunction to discharge the solidified reaction product and obtain the cathode material precursor slurry.
5. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 4, characterized in that, Step S3 further includes the following sub-steps: Step S34, the cathode material precursor slurry is fed into a vacuum filter for solid-liquid separation, and the separated filter cake is washed 3 to 5 times alternately with deionized water and anhydrous ethanol as detergents, and the washed precursor solid is collected; Step S35, the washed precursor solid is placed in a double-layer multi-temperature controlled vacuum drying oven, and is dried at a constant temperature of 60°C to 80°C and a vacuum degree of not less than 0.09MPa for 12 to 24 hours to obtain the long-cycle aqueous zinc-ion battery cathode material.
6. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, The molar ratio of zinc to manganese in the vanadium sulfate aqueous solution is 1:2 to 1:4; and the vanadium sulfate aqueous solution also contains sodium sulfate with a molar concentration of 0.1 mol / L to 0.5 mol / L, which is used as a crystal anisotropic growth guiding agent.
7. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, In step S1, the high-shear cross-flow dispersion channel is realized by a twin-screw grinding cross-flow pump connected in the same direction or a high-shear inline emulsifier, and the electromagnetic pulse feeding valve port for injecting sodium hydroxide precipitant aqueous solution is directly aligned with the fluid shear zone with the greatest shear force inside the high-shear cross-flow dispersion channel.
8. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 1, characterized in that, In step S1, the ambient fluid temperature is maintained between 25°C and 40°C when the vanadium sulfate aqueous solution is pumped into the high-shear cross-flow dispersion channel, and the pumping flow rate of the sodium hydroxide precipitant aqueous solution is controlled between 10 mL / min and 30 mL / min during the high-flow-rate dripping stage.
9. The method for preparing a long-cycle aqueous zinc-ion battery cathode material according to claim 3, characterized in that, In step S2, during the injection of multi-stage doped modifier aqueous solution into the high-shear cross-flow dispersion channel, the external jacketed ultrasonic transducer is turned on to emit ultrasonic waves with a pulse power of 100W to 200W into the reaction fluid inside the high-shear cross-flow dispersion channel, and the timing of the ultrasonic wave activation is controlled to be synchronized with the duration of the zero-flow resting phase.
10. A cathode material for a long-cycle aqueous zinc-ion battery, characterized in that, The positive electrode material for a long-cycle aqueous zinc-ion battery is prepared by the method described in claim 1.
Citation Information
Patent Citations
Novel vanadium-based aqueous zinc ion battery positive electrode and preparation method thereof
CN117878237A